Correlation Between Medical Information Completeness and Accuracy of The Diagnosis Code for Upper Respiratory Tract Infection and Hypertension Based on ICD-10 in Medical Record at Cibening Health Center - Muchlis, Ahmad; Ramadhanty, Rifa Aulia (Muhammadiyah Medical Journal, 2021)
Background: Completeness of patient medical information in medical records is one indicator in assessing the quality of health services. Complete and accurate medical records contribute to the accuracy of medical staff in making a diagnosis so that they can determine the correct diagnosis code according to the ICD-10 guidelines. A good medical record shows that a doctor or other medical staff has carried out their duties by the demands of their profession as stated in the Medical Practice Law No.29 of 2004. Purposes: To find out there is or not a correlation between the medical information completeness and the accuracy of the diagnosis code for upper respiratory tract infection and hypertension based on the ICD-10 in the medical record documents of outpatients at the Cibening Health Center in 2019. Method: The method used in this study is observational analytic with a cross-sectional study design. The population of this study was outpatient medical records with a diagnosis of upper respiratory tract infection and hypertension at the Cibening Health Center in 2019. The sampling technique used a simple random sampling technique with a sample size of 100. Results: Out of obtained 71 complete medical record (71%) filling in medical records, 64 medical records (64%) were accurate in giving ICD-10 codes, 63 medical records (88.7%) with complete medical information had accurate diagnosis codes in comparison with 8 medical records (11.3%) which were complete but inaccurate diagnosis code. Conclusion: With a p-value of 0.000, there is a significant correlation between the completeness of medical information and the accuracy of the diagnosis code for Upper Respiratory Tract Infection and Hypertension based on ICD-10.